Antioxidant power as a quality control marker for completeness of amotosalen and ultraviolet A photochemical treatments in platelet concentrates and plasma units. Issue 7 (17th May 2016) - Abonnenc, Mélanie; Crettaz, David; Tacchini, Philippe; Di Vincenzo, Luciana; Sonego, Giona; Prudent, Michel; Tissot, Jean‐Daniel; Lion, Niels
Abstract : BACKGROUND: Pathogen inactivation treatments such as INTERCEPT aim to make sure blood and blood‐derived products are free of pathogens before using them for transfusion purposes. At present, there is no established quality control assay that assesses the completeness of the treatment. As INTERCEPT is a photochemical treatment known to generate reactive oxygen species we sought to use the antioxidant power (AOP) of the blood product as a marker of treatment execution. In this perspective, we evaluated an electrochemically based miniaturized system, the EDEL technology, for measuring the AOP in both platelet concentrates (PCs) and plasma. STUDY DESIGN AND METHODS: Aliquots were withdrawn from PCs or plasma units before and after INTERCEPT treatment and a few microliters were directly deposited into the EDEL sensor for the AOP measurement. The result is expressed in EDEL, an arbitrary unit (micromolar equivalent of ascorbic acid). RESULTS: The INTERCEPT treatment resulted in a significant decrease of the AOP. An AOP threshold of 66.5, 89.0, 59.8, and 131.5 EDEL was determined for apheresis PCs collected from female and male donors, buffy coat PCs, and plasma units, respectively. Below the threshold value, INTERCEPT treatment is considered to be executed. Additionally, we showed that the presence of the photosensitizer in combination with the ultraviolet A illumination is required to observe the AOP decrease. CONCLUSION: The measurement of the AOP of PCs and plasma units can be used to document the completeness of the INTERCEPT treatment.